Kandungan Fitokimia Daun Asam Jawa dan Potensinya sebagai Bioagen Antibakteri untuk Pengobatan Alami - Karmana, I Wayan (Biocaster : Jurnal Kajian Biologi, 2024)
Indonesia is known as a country that is abundant in various biological riches and their potential as medicines, so a review of natural antidiarrheal treatment methods using tamarind leaves was carried out. Diarrhea is a digestive disorder with a high prevalence rate, especially in developing countries. Diarrhea is a digestive system disorder characterized by stomach cramps, a liquid stool consistency, and an increase in the frequency of defecation more than 3 times in 24 hours. The research method used is to use literature review through online publications based on the Web, ResearchGate, Google Scholar and Scopus. The research sample used in this literature review was 22 articles. The research results show that the phytochemical content of tamarind consists of tannins, flavonoids, saponins, alkaloids, phenols and triterpenoids. The results of the analysis in the literature review show that tamarind leaves are an alternative natural treatment and are effective in inhibiting the growth of bacteria, for example the Escherichia coli bacteria that causes diarrhea.